Analysis of warpage on front panet panel housing using response surface method - Mohd Afiq Harun (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
In injection moulding process, moulded plastic parts is consider one of the most econmical manufacturing process with high volume of plastic parts produces. Causes of variations in injection moulding are related to the vast number of factors acting during a regular production run, which directly impacts the quality of final products.